“Simpati: Siap mencegah Penyakit Hipertensi” di Kelurahan Kebon Waru Kota Bandung - Setiawan, Shellita Melanie Astuti; Wardhana, Yodi; Pura, Intan Salsabila; Karyana, Mey Meylani; Shafira, Dinda Adhita; Allatif, Denden; Lestari, Nabila Zahra (Penerbit Goodwood, 2024)
Purpose: Hypertension is known as